Providing specimens of sanitary ware and socket outlet of basement - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding providing specimens of sanitary ware and socket outlet of basement of BRAC University new campus project.